Respostas estruturais e de trocas gasosas em folhas de Gochnatia barrosii (Cabrera). (Asteraceae) ocorrente em diferentes ambientes de cerrado - Almeida, Ana Carolina Melo de (2019)
The knowledge of factors that determine the ecological distribution of plants is very important for the species conservation. Alto Rio Grande has vegetation with forest patches, campo rupestre and cerrado, and this physiognomic variation of vegetation is due to the region shelters one of the transition areas between the Cerrado of Central Brazil and the semideciduous forests of the Southeast and South of the country. The Gochnatia barrosii (Asteracaeae) species occurs in these varied environments, with capacity to adapt in different phytophysiognomies, indicating a possible phenotypic plasticity. Thus, the objective of this study was to analyze the anatomy and gas exchange of leaves of G. barrosii, in different physiognomies of Parque Ecológico Quedas do Rio Bonito, Lavras - MG. The leaves of 5 individuals were collected from three different areas: 1) Cerrado; 2) Rocky field and 3) Transition Forest - Cerrado. The collected material was prepared, and made paradermic and transverse sections. After, the material was photographed using microscope for analysis. The gas exchanges were evaluated in the field, using the equipment IRGA. The specific leaf area (SLA) was also obtained. The data were analyzed through the Linear Mixed Effects Models (MEML), where the response variables were those of the plant and the explanatory variable the environments. The models were submitted to Analysis of Variance (ANOVA p <0.05) with the Satterthwaite method and the normality and homoscedasticity of the residues tested through Shapiro-Wilk and Breusch-Pagan, respectively. LS-means generic function (Rune Haubo B. Christensen) was used to compare the means in the different environments. In addition, the response variables were submitted to Pearson correlation analysis (p <0.05) and those with significant correlation with SLA were submitted to linear regression analysis. The Relative Distance Plasticity Index (RDPI) was also obtained. There was no influence of the environments on the gas exchange characteristics of G. barrosii. It was observed a greater thickness of the adaxial epidermis in leaves of the cerrado, and of the abaxial in leaves of the rocky field and transition. The stomatal density was higher in the rocky field, while the polar diameter was lower in this environment. The smallest equatorial diameter was observed in the cerrado leaves. There were higher averages for trichome density in leaves from the rocky field and transition. The palisade parenchyma and leaf blade presented thicker leaves in the transition area and the spongy parenchyma was thicker in the Cerrado leaves. On the other hand, the leaves of the transition area had the lowest mean values for SLA. The proportion of xylem and phloem in the main leaf vein was not affected by the different collection environments. The density of trichomes of the abaxial face presented the highest RDPI. The structural modifications in the leaves of G. barrosii indicate that the species has anatomical plasticity that may have contributed to the maintenance of the gas exchange between the different environments of Cerrado.